Gambaran Regulasi Emosi pada Pegawai Pengadilan Agama Bagian PTSP ( Pelayanan Terpadu Satu Pintu) - Mellani Agustin; Endah Fajri Arianti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Religious courts are first-level courts that are tasked and authorized to examine, decide, and resolve cases at the first level between people who are Muslim, both in the fields of marriage, inheritance, wills, gifts and applications for adoption, applications for marriage dispensation for underage marriages. The research used by the researcher is a qualitative approach. Emotional regulation is the process by which individuals manage, experience, and express emotions. Emotional regulation of men and women has differences, namely that women's emotions express emotions more to maintain their interpersonal relationships so that women appear weaker, but men express them more with anger and pride so that they show more dominance.